A multipurpose biochip for food pathogen detection. Issue 15 (17th March 2016) - Primiceri, Elisabetta; Chiriacò, Maria Serena; de Feo, Francesco; Santovito, Elisa; Fusco, Vincenzina; Maruccio, Giuseppe
Abstract : We realized an innovative biosensing platform with high sensitivity, low-cost and label-free features for S. aureus and L. monocytogenes detection from meat. Abstract : Foodborne illnesses caused by the ingestion of foods contaminated with pathogens and/or their toxins are still one of the major public health threats worldwide. Disposable devices, allowing the on-site, early and multiplexed quantitative detection of pathogenic bacteria are therefore highly sought. Herein, we report biochips that are able to quantitatively detect two of the most common food-associated pathogens, namely Listeria monocytogenes and Staphylococcus aureus from the suspensions of bacteria stationary-phase broth culture. With a detection limit as low as 5.00 CFU ml −1 for L. monocytogenes and 1.26 CFU ml −1 for S. aureus, our platform may be a promising point-of-care device not only for clinical and food diagnostics but also for biosecurity purposes.